Effect of Tamsulosin versus Placebo in Females with Lower Urinary Tract Symptoms Less Than 40 Years of Age - Aman Ullah; Murtaza, Badar; Khan, Haroon Sabir; Khan Muhammad; Khan, Ajmal; Tahir, Muhammad (Indus Journal of Bioscience Research, 2025)
Introduction: LUTS in women chronically affects the quality of life, and, to combat it, few treatment methods are available to women below the age of 40. Tamsulosin is an alpha-1 adrenergic blocker commonly used in men whereas young women with LUTS are under-studied. Objective: To compare the average response of International Prostate Symptom Score (IPSS) due to treatment using Tamsulosin and Placebo in females less than 40 years and with LUTS after 4 weeks of treatment. Material and methods: This was a prospective, comparative cross-sectional study done in AFIU, Rawalpindi from 12th April, 2025 to 12th July, 2025. One hundred and thirty six patients were randomly assigned to take Tamsulosin 0.4 mg or placebo daily once in a period of 4 weeks. The scores of IPSS before and after treatment were noted and compared. Results: The improvement of the IPSS was substantially superior in the Tamsulosin group (7.9 + 2.8) than in the placebo (2.4 + 2.5; p < 0.001). It was a well-tolerated treatment. Conclusion: Tamsulosin is a safe and effective therapy of LUTS syndrome in young girls